PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN MODEL PEMBELAJARAN BERBASIS MASALAH PADA MATERI PERBANDINGAN KELAS VII SMP/MTs - Sukri, Metti; Siregar, Syarifah Nur; ', Syofni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this study is the restrict of mathematics instrument as supporting referring to 2013 curiculum. This study has purpose to develop mathematics learning instruments as lesson plans and student worksheet with problem based learning’s model on comparison of class for 7th grade junior high school. This method used are 4D model by Define, Design, Develop, Disseminate. But, in this study only to third step or develop step. A learning instruments was validating by three validator and then fix based on validator’s suggestion. Lesson plans that has validated, then trials to small group consist of eight students from SMP Negeri 1 Kuantan Mudik. Based on the data analysis, it can be conclude that mathematics learning instruments is very valid with mean score of lesson plans is 3,71 and mean score of student worksheet is 3,76. This student worksheet has also reached the practical qualification with mean percentage of student respone is 94,37 on small test group.Keyword: Mathematics Learning Instrument, Problem Based Learning, Comparison.